Bede : On Genesis - Beda Venerabilis, asi 672-735 (Translated texts for historians ;, 2008)
This is the first English translation of the Venerable Bede’s commentary on the book of Genesis. Dealing as it does with the biblical account of the creation of the world and of mankind, and of mankind’s fall from grace and exile into the life of time, On Genesis offers essential insights into Bede’s fundamental assumptions as a theologian, historian, and scientific cosmologist. Bede’s role in laying the foundations of the modern world cannot be overemphasised. From his quantitative approach to questions of science to his introduction of the Anno Domini system of dating and his text-critical methods of biblical analysis, he anticipated and influenced modern ways of thinking. Bede regarded the opening chapters of Genesis as the foundation narrative of the world. From it Bede derived the theoretical basis for his scientific treatises and his notion of the English as a chosen people of God, which informs the Ecclesiastical History. This translation and introduction attempts to make Bede’s commentary accessible to anyone with an interest in his work.